Biting myself so I don’t bite the dust: prevalence and predictors of deliberate self-harm and suicide ideation in Azorean youths - Barreto Carvalho,Célia (2017)
Objective: To characterize non-suicidal self-injury (NSSI) behaviors, methods, and functions as well as suicide ideation in the adolescent population of a Portuguese community in São Miguel Island, Azores. Increasing rates of NSSI behaviors among adolescents have been observed globally, while suicidal behavior has been pointed as a major cause of death during adolescence. Methods: A sample of 1,763 adolescents, aged 14 to 22, was randomly drawn from public and private schools and administered a set of self-report questionnaires. Descriptive and regression analyses were used to look for specific relationships and predictors of NSSI and suicide ideation in this isolated community. Results: Approximately 30% of youths reported at least one NSSI behavior, a rate that is twice as high as most studies carried out in mainland Portugal and in other European countries. Biting oneself was the most frequent form of NSSI, and NSSI behaviors served predominantly automatic reinforcement purposes (i.e., regulation of disruptive emotional states). NSSI and suicide ideation encompassed different distal and proximal risk factors. Conclusions: Exploring and characterizing these phenomena is necessary to provide a better understanding, enhance current conceptualizations, and guide the development of more effective prevention and intervention strategies in youths.